Faktor-Faktor Yang Berhubungan Dengan Pemilihan Tempat Pertolongan Persalinan Pada Ibu Bersalin - Pawiliyah, Pawiliyah; Susanti, Epi (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
Labor events are physiological events whose processes can run smoothly and safely if the helper in labor can monitor labor to detect complications early. The purposeÂ of this study was to look at the factors related to the selection of Birth assistance places for labor mothers in Lingkar Timur Public Health Center of Bengkulu City. This study used descriptive correlational using Cross Sectional design. The sample in this study was taken by using purposive sampling technique that is taking as many as 78 samples. Data were tested using the chi-square test. To determine the closeness of the relationship, a contingency coefficient (C) test has been used. There is a relationship between age with the selection of birth assistance places in labor mothers in the Lingkar Timur Public Health Center in Bengkulu City with p=0,000 0,05 a close relationship category. There is a relationship of parity with the selection of birth places in delivery mothers in the Lingkar Timur Public Health Center Work Area with p=0,003 0,05 medium relationship category. There is an educational relationship with the selection of birth places in delivery mothers in Lingkar Timur Public Health Center with p=0,000 0,05 in the category of close relationships. There is a relationship between the complication of labor and the choice of place of delivery assistance for women giving birth in Lingkar Timur Public Health Center of Bengkulu City with p=0,000 0,05 a close relationship category. Based on the results of the study recommends the importance of health promotion such as Antenatal care, conducting pregnant mothers class programs, so that pregnant women get information and knowledge about their pregnancy conditions and can choose the right place of delivery according to their pregnancy conditions.